Graph-Augmented Deep Hashing for Large-Scale Multi-Label Image Retrieval with Adaptive Margin Constraints - Huawen Guo; Finn C. Eriksson (International Journal of Clinical and Translational Medicine, 2026)
The exponential growth of multi-label image collections in domains ranging from medical diagnostics to autonomous systems demands retrieval mechanisms that are simultaneously efficient, semantically precise, and adaptable to evolving label spaces. Deep hashing has emerged as a cornerstone of large-scale approximate nearest neighbor search, converting high-dimensional visual features into compact binary codes. However, conventional deep hashing models often overlook the rich interdependencies among multiple labels and rely on rigid similarity thresholds that fail to capture the graded semantic relationships inherent in multi-label annotations. This paper presents a system-level investigation of graph-augmented deep hashing architectures that integrate graph neural networks to explicitly model label co-occurrence and conditional dependencies, combined with adaptive margin constraints that calibrate the Hamming embedding space according to the degree of semantic overlap between samples. The discussion centers on structural trade-offs within the full retrieval pipeline, from graph construction and feature fusion to hash code optimization and distributed index serving. We analyze the infrastructure requirements for training and inference at scale, examine robustness under label noise and adversarial perturbations, and probe fairness implications arising from long-tail category distributions. Governance challenges including auditability, consent-aware data management, and the sustainability of energy-intensive hashing training cycles are critically evaluated. By synthesizing architectural insights with deployment realities, the work offers a forward-looking perspective on building responsible, resilient, and scalable multi-label image retrieval systems.